Teknologi Tepat Guna Pembuatan Kripik Dari Umbi-Umbian - Azwar Anwar; Hajrah Hamzah (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. This Community Partnership Program (PKM) partner is a Bumdes and community of fishermen's wives in Munte Village. Partner problems are: (1) lack of knowledge about processing tubers into processed products that have high selling value, (2) lack of skills in making chips that can be used as additional family income, (3) quality of chips production from tubers of economic value very limited height. The target of the program is tuber chips that have a high selling / economic value so that fishermen's wives have additional income. The methods used are: lectures, demonstrations, discussions, questions and answers, and companion partners. The results achieved are (1) partners have knowledge in processing tubers into food products of high economic value, (2) partners have the skills to make marketable chips, (3) partners have the ability to increase the production of chips to be used as additional family income.